Modern Seed Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Satisfying the increasing number of consumer demands for high-quality seeds with enhanced performance is one of the most imperative challenges of modern agriculture. In this view, it is essential to remember that the seed quality of crops does not improve.